2005
DOI: 10.1136/bjo.2004.055822
|View full text |Cite
|
Sign up to set email alerts
|

Decreased tear lipocalin concentration in patients with meibomian gland dysfunction

Abstract: Background/aim: Recent studies have demonstrated that tear lipocalin (TL) and phospholipids have a crucial role in maintaining tear film stability. The level of TL in patients with meibomian gland dysfunction (MGD) was examined and these data were correlated with the severity of their clinical disorder. Methods: 12 patients with obstructive MGD, 12 patients with seborrhoeic MGD, and 12 age matched normal control subjects participated in this study. 3 ml of unstimulated tears were collected with a micropipette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…Lipocalin decrease is in agreement with previous studies performed in patients suffering from Sjogren's Syndrome 28 and Meibomian Gland Dysfunction. 29 To our knowledge, the decrease in the abundances of lipophillin A-B observed in our study has never been described before and may constitute a further progress in the identification of mechanisms responsible for the stability of human tears.…”
mentioning
confidence: 76%
“…Lipocalin decrease is in agreement with previous studies performed in patients suffering from Sjogren's Syndrome 28 and Meibomian Gland Dysfunction. 29 To our knowledge, the decrease in the abundances of lipophillin A-B observed in our study has never been described before and may constitute a further progress in the identification of mechanisms responsible for the stability of human tears.…”
mentioning
confidence: 76%
“…We recently reported that concentrations of tear lipocalin in patients with meibomian gland dysfunction are significantly lower than in normal controls. 18 Tear lipocalin concentration correlated positively with tear film BUT and negatively with fluorescein staining scores in these patients. On the other hand, Grus et al 19 reported that lipocalin concentrations are somewhat elevated in the tears of contact lens wearers versus in normal controls, and Glasson et al 20 reported that contact lens-intolerant subjects had significantly higher amounts of lipocalin in tears compared with subjects who were able to tolerate contact lens wear.…”
mentioning
confidence: 96%
“…3 Lysozyme was decreased in blepharitis patients, 4 lactoferrin was lower in Sjögren and Stevens-Johnson syndromes, 5 and reduced lipocalin has been found in patients with seborrheic blepharitis and meibomian gland dysfunction. 6 Such observations have led to the concept that in addition to antibacterial function, certain tear proteins themselves can act as regulators of tear secretion, growth factors, or essential elements for renewal of ocular epithelia.…”
mentioning
confidence: 99%